Pengaruh Aktivitas Bermain Media Konkrit terhadap Kemampuan Membilang di Kelompok B TK Aba Purworejo - Yuli Haryati; Ismartoyo Ismartoyo; Aini Indriasih (STKIP PGRI SITUBONDO, 2022)
Kindergarten of early Childhood education has a role as the basis for the ability of children to prepare for education at the next level. For this reason education in kindergarten is expected to provide astrong foundation or basis in order to develop all aspects of the development of children holistically. In order for children for children to develop as expected, learning in kindergarten should be planned as a process toward further development in the most affective and efficient way, so that children are ready to attend education at a higher level. Furthermore, in order to prepare the children for attending higher education level, including in learning to apply playing strategies using various concrete media, with the hope that children’s ability in counting will be more developed than before. From this study, the authors know that the use of concrete media has given aquite large effect on the group of children who are treated to play activities with those who are not treated in counting activities